A graduate student characteristic study in the College of Education, University of the Philippines - Mangindaan, Christina S. 1938- (s.n.], 1971)
The characteristics of the students enrolled at the College of Education in the University of the Philippines were analyzed in terms of the following: academic background, parents educational attainment, financial status, perceived problems of adjustment, assessment of the college atmosphere, participation in social activities, motivational attitudes towards teaching. It also sought to find what information services for the graduate students could be suggested by these characteristics. A questionnaire was specifically constructed for this study. The items in the questionnaire were adapted from Astin and Mori studies.